Song exposure during juvenile dispersal in Mountain White-crowned Sparrows. (19th March 2014) - Ho, Winnie W.; Connolly, Sara G.; Reynolds, Pamela L.; Cornelius, Jamie M.; MacDougall-Shackleton, Elizabeth A.; Morton, Martin L.; Pereyra, Maria E.; Hahn, Thomas P.
Abstract: The degree to which local song structure reflects the singer's population of origin is a long-standing and contentious issue. Young songbirds that settle to breed outside their natal song-dialect area may learn to produce nonnatal dialect by hearing and memorizing these songs during juvenile dispersal. We quantified adult singing rates in a population of Mountain White-crowned Sparrows ( Zonotrichia leucophrys oriantha ) in the Sierra Nevada in 2 yr, and compared them with the arrival schedule of juveniles not hatched on the study area. Our results show that opportunities for juveniles to learn new (nonnatal) song types become highly limited during the premigratory dispersal phase, because adult singing rates are very low by the time nonlocal juveniles begin to arrive. Thus, if individuals learn nonnatal songs during dispersal, they must do so hearing relatively few repetitions of the unfamiliar dialect.